Introducing very young children to English as a foreing language - Scheffler, Paweł (Wiley, 2015)
This article describes how two very young Polish children were introduced to English through children’s animation series, with meaning being made clear through translation. The children were first exposed to English input at the age of 21 months, and when they were four years and three months old, all their English utterances were collected over a period of six weeks. The children’s use of language is compared with utterances produced by children attending monolingual English instruction in a formal setting. The comparison shows a more spontaneous and creative use of English by the children in this study. This indicates that a bilingual approach in which children simply experience a foreign language at home may be more effective than monolingual teaching in a formal setting.
Keywords: learning English with Peppa Pig; co-viewing animated programs with young learners of English; preschool learners of English; very young learners of English